Fiqh and Siyasa Model of Integration: A Study of The Constitution of The Sultanate of Aceh Darussalam - Sabil, Jabbar (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Fiqh is an abstract concept not bound to a particular case in space and time, so it becomes universal. Through a legal decision, the judiciary applies Fiqh to one of the cases in particular. It shows that Fiqh implementation requires other legal instruments, such as the judiciary. The implementation aspect of Fiqh is an object study for Siyasa Sharia, so Fiqh and Siyasa had to moderate and integrate into the law system. This paper examines the moderation of Fiqh and Siyasa in the Aceh Darussalam Sultanate and their integration into the legal system. This study is normative legal research that uses a historical approach. The data source for this research is primary legal material in the form of the constitutional text of the Sultanate of Aceh Darussalam, namely Adat Meukuta Alam, and other supporting texts. This study found that the constitution of the Aceh Darussalam Sultanate drew on moderate Fiqh and Siyasa. The results of this study conclude that Fiqh and Siyasa were integrating into a legal system that complements one another